Prologue - Durazo-Watanabe, Eduardo (My University, 2024)
Innovation and entrepreneurship have long served as catalysts for progress, shaping how societies evolve, adapt, and thrive in an ever-changing world. In the face of emerging global challenges—ranging from sustainability concerns to digital transformation—the role of research in fostering new economic paradigms has never been more crucial. The XV National Congress of the Red de Investigación y Docencia en Innovación Tecnológica (RIDIT) stands as a testament to the importance of academic collaboration in driving meaningful change. By providing a platform for scholars, educators, and industry professionals, RIDIT fosters critical discussions that shape the future of innovation and technology.
Keywords: Innovation; Entrepreneurship; Campus Ensenada